Basic development construction companies in the conditions of transformation economy - I. A. Prudnikov; A. M. Rotar (Путеводитель предпринимателя)
The Theory of crisis management in construction suggests that the company performs a number of measures aimed at combating the crisis. Many of them are well known. For example, a reactive approach with its practice of cutting salaries, layoffs, compression of structural units of companies. The construction company is one of the main industries that is able to solve social, economic and technological problems in the development of the national economy ofRussia. In order for the company to successfully cope with all the tasks and achieve all the goals, it is necessary to clearly coordinate the organization within the enterprise. The article analyzes the main methods of development of construction companies in the transformation of the economy.